The chronicles of Narnia the lion, the witch and the wardrobe - Johnson, Mark; Steuer, Philip; Adamson, Andrew; Walt Disney Pictures; Walden Media (Burbank, CA : Walt Disney Home Entertainment : distributed by Buena Vista Home Entertainment, 2006)
When Lucy Pevenise, her older brothers Edmund and Peter, and her older sister Susan are sent to the country for safer keeping during the initial bombing raids of WW II, they decide to play hide-and-seek in the strange house of the mysterious professor.During the game Lucy discovers a mysterious wardrobe and discovers an entirely different world. The place is called Narnia, and it's been locked in winter for over 100 years by someone known as'The White Witch'
Title from title screen
Based on the book by C.S. Lewis
Director of photography, Donald M. McAlpine ; music composed by, Harry Gregson-Williams ; edited by, Sim Evan-Jones ; costume designer, Isis Mussenden ; production designer, Roger Ford
Georgie Henley, Skandar Keynes, William Moseley, Anna Popplewell, Tilda Swinton, James McAvoy, Jim Broadbent, Kiran Shah, James Cosmo, Judy McIntosh, Elizabeth Hawthorne, Patrick Kake
With Malay subtitles
Keywords: Narnia (Imaginary place) -- Drama; Brothers and sisters -- Drama; Witches -- Drama